Regional Disparities in Medical Personnel Distribution: A Case Study of Surkhandarya: Kesenjangan Regional dalam Distribusi Tenaga Medis: Studi Kasus Surkhandarya - Utanovna, Pardayeva Sarvinoz (Indonesian Journal of Innovation Studies, 2023)
This study delves into the geography of medical services in the Surkhandarya region, focusing on the distribution of medical personnel across various districts. The research utilizes statistical data to analyze the ratio of doctors to the population in different areas, revealing significant disparities. The region boasts 92 hospitals, 366 polyclinics, and numerous other medical institutions, staffed by 4,200 doctors and 17,600 secondary medical workers. However, the distribution of these professionals varies widely, with the highest doctor-to-population ratio in Termiz city and the lowest in districts like Muzrabot and Bandikhon. The study also highlights the role of non-governmental institutions and international organizations in bolstering the regional healthcare system. The findings underscore the need for a more balanced distribution of medical personnel across the region, which could significantly enhance healthcare accessibility and quality. This research has implications for healthcare planning and policy, emphasizing the importance of considering geographical factors in medical resource allocation.Highlights: Significant disparities exist in the distribution of medical personnel across the Surkhandarya region, with some areas having a higher doctor-to-population ratio than others. Non-governmental institutions and international organizations play a crucial role in supplementing the regional healthcare system. The study's findings underscore the need for more balanced resource allocation in healthcare, taking geographical factors into account. Keywords: Medical personnel distribution, healthcare geography, Surkhandarya region, doctor-to-population ratio, healthcare policy.